(untitled) (Education in the 21st Century, 2023)
Italy actively participates in the process of forming the European Higher Education Area, successfully implements an internationalization strategy, while maintaining the characteristics of national education. The modern system of quality assurance of higher education in Italy includes the state and public structures interested in the quality of education, the quality management of the universities themselves and the mechanisms of interaction with pan-European agencies. Each Italian university has a quality assessment department that independently monitors the quality assessment processes of educational programs, and the quality of higher education educational programs is considered a national priority. The Ministry of Education, Universities and Science established the National Institute for the Evaluation of the Higher Education System (INVALSI, Instituto Nazionale per la Valutazione del Sistema dell’Istruzione) for the activities of the university units for the control of the quality of education. In 1999, a special intermediary organization, the National Committee for the Evaluation of the Higher Education System (CNVSU), was created, whose task is to verify the conformity of the level of Italian higher education with pan-European standards. Other public bodies also participate in the process of quality assessment of education, such as the National Council of Universities (Consiglio Universitario Nazionale - CUN), the Conference of Rectors of Italian Universities CRUI (Conferenza dei Rettori delle Università Italiane), the National Committee for Quality Assessment of Italian Universities - CONVUI (Coordinamento Nazionale dei Nuclei di Valutazione delle Università Italiane), National Student Council - (Consiglio Nazionale degli Studenti Universitari – CNSU). The state defines the minimum standards of accreditation developed for educational programs, which contain border concepts of recognition of the quality of educational programs.